E-Learning platform and its role in increasing road safety awareness - Darabi Golshani, Ali Mohammed; Nikravan, Z.; Nikraz, Hamid (International Association of Technology, Education and Development (IATED), 2010)
Road traffic accidents represent the third leading cause of death and disease worldwide according to the World Health Organisation (WHO). Many countries in the world have launched safety campaigns that are intended to reduce road traffic accidents by increasing public awareness. Traditional methods of education have been employed in the majority of safety campaigns. In recent years electronic learning (e-learning) platforms have created new dimensions in teaching and learning. The most notable platforms are Blackboard, WebCT and Moodle. Blackboard andWebCT are commercial e-learning course management softwares, whereas Moodle is freely available open source software. All e-learning platforms provide users with varieties of facilities such as electronic presentation,course/unit information, learning resources, video of lecture, library resources, internet resources, interactive whiteboard, virtual learning environment, learning activities, communications (email, discussion board, etc.) and many other features. This paper would examine the role of e-learning platforms and how this technology could assist such campaigns to become more effective and successful.